Car, LDR and Third Party Funds on the Amount of Credit Disbursed by Rural Banks in North Sumatera, Indonesia - Magdalena Judika Siringoringo; Jadongan Sijabat (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The amount of credit disbursed in several BPRs in 12 regencies / cities in 2017-2021 has decreased, where this decrease is due to the ability of several BPRs in 12 regencies / cities to increase capital adequacy (CAR) and the ability of BPRs to increase the amount of third party funds is not optimal and tends to decrease, although the ability of some BPRs to increase the amount of credit income that has been channeled has actually increased, but the increase in LDR is not able to increase the amount of credit that has been channeled to the community, so that the efforts of some BPRs in maximizing the use of funds for the process of lending to the community are not running properly. The type of research used is quantitative descriptive research. The research methodology used is multiple linear regression analysis. The results showed that partially only the CAR variable and the third party funds variable had a positive and significant effect on the amount of credit channeled by 12 BPRs in 12 regencies / cities in North Sumatra Province in 2017-2021 and simultaneously the CAR, LDR and third party funds variables had a positive and significant effect on the amount of credit channeled by 12 BPRs in 12 regencies / cities in North Sumatra Province in 2017-2021. Testing the adjusted coefficient of determination (Adjusted R Square) obtained a value of 0.851, meaning that the independent variables, namely CAR, LDR and third party fund variables, have an effect of 85.1% on the dependent variable, namely the amount of credit disbursed by 12 BPRs in 12 regencies / cities in North Sumatra Province in 2017-2021.